Transduodenal Endosonography-Guided Biliary Drainage and Duodenal Stenting for Palliation of Malignant Obstructive Jaundice and Duodenal Obstruction - Maluf-Filho, Fauze; Retes, Felipe Alves; Neves, Carla Zanellato; Sato, Cezar Fabiano Manabu; Kawaguti, Fabio Shiguehissa; Jureidini, Ricardo; Ribeiro Jr, Ulysses; Bacchella, Telesforo (JOP. Journal of the Pancreas, 2012)
Context Endosonography-guided biliary drainage has been used over the last few years as a salvage procedure when endoscopic retrograde cholangiopancreatography fails. Malignant gastric outlet obstruction may also be present in these patients. We report the results of both procedures during the same session in patients with duodenal and biliary obstruction due to malignant disease. Methods A retrospective review from a prospective collected database. Results Technical success was achieved in all five patients; however, only three patients experienced relief of jaundice and gastric outlet obstruction. Conclusions Endosonography-guided biliary drainage and duodenal stenting in the same session is feasible. However, severe complications may limit the procedure. This is a challenging procedure and should be done by experts with special attention to patient’s selection.